2000
DOI: 10.1117/12.406610
|View full text |Cite
|
Sign up to set email alerts
|

Using blocks of skewers for faster computation of pixel purity index

Abstract: an affirmative action/equal opportunity employer, is operated by the University of California for the U.S. Department of Energy under contract W-7405-ENG-36. By acceptance of this article, the publisher recognizes that the US. Government retains a nonexclusive, royaltyfree license to publish or reproduce the published form of this contribution, or to allow others to do so, for U.S. Government purposes. Los Alamos National Laboratory requests that the publisher identify this article as work performed under the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…N-FINDR and PPI were coded accordingly to [38] and [33], respectively. Regarding PPI, the number of skewers must be large [39], [40], [49]- [51]. Based on Monte Carlo runs, we concluded that the minimum number of skewers beyond which there is no unmixing improvements is about 1000.…”
Section: Evaluation Of the Vca Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…N-FINDR and PPI were coded accordingly to [38] and [33], respectively. Regarding PPI, the number of skewers must be large [39], [40], [49]- [51]. Based on Monte Carlo runs, we concluded that the minimum number of skewers beyond which there is no unmixing improvements is about 1000.…”
Section: Evaluation Of the Vca Algorithmmentioning
confidence: 99%
“…The algorithm then projects every spectral vector onto skewers (large number of random vectors) [33], [40], [41]. The points corresponding to extremes, for each skewer direction, are stored.…”
Section: Introductionmentioning
confidence: 99%
“…8. A software approach for fast PPI was discussed by Theiler et al 80 which expanded a small set of "direct dot products" into a larger set of "derived dot products." Although this approach was originally designed as a software speedup, and as such was a "competitor" to the hardware implementation, Fig.…”
Section: Endmembers and Pixel Purity Indexmentioning
confidence: 99%
“…The user is thus enabled to explore the behavior of the algorithm under different conditions. Papers by Theiler et al 27,28 in this volume give more details on the project.…”
Section: Spectral Processing Applicationsmentioning
confidence: 99%